Thioridazine Induces Cardiotoxicity via Reactive Oxygen Species-Mediated hERG Channel Deficiency and L-Type Calcium Channel Activation. (23rd January 2020) - Liu, Yan; Xu, Xueqi; Zhang, Yuhao; Li, Mingzhu; Guo, Jiamengyi; Yan, Caichuan; Wang, Fang; Li, Yuexin; Ding, Yunqi; Li, Baoxin; Fan, Pan
Abstract : Thioridazine (THIO) is a phenothiazine derivative that is mainly used for the treatment of psychotic disorders. However, cardiac arrhythmias especially QT interval prolongation associated with the application of this compound have received serious attention after its introduction into clinical practice, and the mechanisms underlying the cardiotoxicity induced by THIO have not been well defined. The present study was aimed at exploring the long-term effects of THIO on the hERG and L-type calcium channels, both of which are relevant to the development of QT prolongation. The hERG current (I hERG ) and the calcium current (I Ca ‐ L ) were measured by patch clamp techniques. Protein levels were analyzed by Western blot, and channel-chaperone interactions were determined by coimmunoprecipitation. Reactive oxygen species (ROS) were determined by flow cytometry and laser scanning confocal microscopy. Our results demonstrated that THIO induced hERG channel deficiency but did not alter channel kinetics. THIO promoted ROS production and stimulated endoplasmic reticulum (ER) stress and the related proteins. The ROS scavenger N-acetyl cysteine (NAC) significantly attenuated hERG reduction induced by THIO and abolished the upregulation of ER stress marker proteins. Meanwhile, THIO increased the degradation of hERG channels via disrupting hERG-Hsp70 interactions. The disordered hERG proteins were degraded in proteasomes after ubiquitin modification. On the other hand, THIO increased I Ca ‐ L density and intracellular Ca 2+ ([Ca 2+ ]i ) in neonatal rat ventricular cardiomyocytes (NRVMs). The specific CaMKII inhibitor KN-93 attenuated the intracellular Ca 2+ overload, indicating that ROS-mediated CaMKII activation promoted calcium channel activation induced by THIO. Optical mapping analysis demonstrated the slowing effects of THIO on cardiac repolarization in mouse hearts. THIO significantly prolonged APD50 and APD90 and increased the incidence of early afterdepolarizations (EADs). In human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs), THIO also resulted in APD prolongation. In conclusion, dysfunction of hERG channel proteins and activation of L-type calcium channels via ROS production might be the ionic mechanisms for QT prolongation induced by THIO.